Cyanidin chloride protects mice from methicillin-resistant Staphylococcus aureus-induced pneumonia by targeting Sortase A - Xin Su; Hangqian Yu; Xingye Wang; Chi Zhang; Heming Wang; Xiangri Kong; Yishen Qu; Yanhe Luan; Ying Meng; Jiyu Guan; Guangqi Song; Li Wang; et al. (Virulence, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) has been developing rapidly in recent years. It poses a severe peril to global health care, and the new strategies to against the MRSA is urgently needed. Sortase A (SrtA) regulates the anchoring of many surface proteins. Compounds repress Staphylococcus aureus (S. aureus) cysteine transpeptidase SrtA are considered adequate potent virulence inhibitors. Then, we describe the identification of an effective SrtA inhibitor, cyanidin chloride, a bioflavonoid compound isolated from various plants. It has a reversible inhibitory effect on SrtA activity at an IC50 of 21.91 μg/mL. As a SrtA inhibitor, cyanidin chloride antagonizes SrtA-related virulence phenotypes due to its breadth and specificity, including fibrinogen adhesion, A549 cell invasion, biofilm formation, and surface protein (SpA) anchoring. Subsequently, molecular docking and fluorescence quenching revealed that SrtA and cyanidin chloride had robust mutual affinity. Further mechanistic studies revealed that Arg-197, Gly-167, and Sep-116 were the key-binding sites mediating the interaction between SrtA and cyanidin chloride. Notably, a significant therapeutic effect of cyanidin chloride in vivo was also observed on the mouse pneumonia model induced by MRSA. In conclusion, our study indicates that cyanidin chloride potentially represents a new candidate SrtA inhibitor for S. aureus and potentially be developed as a new antivirulence agent.